Variacions sobre la sort d’un dèu ferit - Valentí Pou, Agnès (Dialogoi. Rivista di studi comparatistici, 2021)
This article is a particular version of the greek myth about the god-hero Asclepius, grandson of Zeus and son of Apollo, where the photographic look and the poetic composition are melted to recreate a personal story about the myth of the Medicine’s ivinity. This recreation, conceived from different poetic voices and different points of view, wants to claim the fate of this benevolent god, always conditioned by the judgement, passions and ambitions of his ancestors.